Maternal parenting predicts infant biobehavioral regulation among women with a history of childhood maltreatment. (12th March 2014) - Martinez-Torteya, Cecilia; Dayton, Carolyn J.; Beeghly, Marjorie; Seng, Julia S.; McGinnis, Ellen; Broderick, Amanda; Rosenblum, Katherine; Muzik, Maria
Abstract: Early biobehavioral regulation, a major influence of later adaptation, develops through dyadic interactions with caregivers. Thus, identification of maternal characteristics that can ameliorate or exacerbate infants' innate vulnerabilities is key for infant well-being and long-term healthy development. The present study evaluated the influence of maternal parenting, postpartum psychopathology, history of childhood maltreatment, and demographic risk on infant behavioral and physiological (i.e., salivary cortisol) regulation using the still-face paradigm. Our sample included 153 women with high rates of childhood maltreatment experiences. Mother–infant dyads completed a multimethod assessment at 7 months of age. Structural equation modeling showed that maternal positive (i.e., sensitive, warm, engaged, and joyful) and negative (i.e., overcontrolling and hostile) behaviors during interactions were associated with concurrent maternal depressive symptoms, single parent status, and low family income. In turn, positive parenting predicted improved infant behavioral regulation (i.e., positive affect and social behaviors following the stressor) and decreased cortisol reactivity (i.e., posttask levels that were similar to or lower than baseline cortisol). These findings suggest increased risk for those women experiencing high levels of depressive symptoms postpartum and highlight the importance of maternal positive interactive behaviors during the first year for children's neurodevelopment.